Dying, assisted death and mourning - Kasher, Asa (At the interface/probing the boundaries. Making sense of dying and death, 2009)
Dying and death are topics of deep humane concern for many people in a variety of circumstances and contexts. However, they are not discussed to any great extent or with sufficient focus in order to gain knowledge and understanding of their major features and aspects. The present volume is an attempt to bridge the undesirable gap between what should be known and understood about dying and death and what is easily accessible. Included in the present volume are chapters arranged in three sections. First, there are chapters on aspects of dying, written by people who have professional experience and.